Tunnelling and its effects on piles and piled structures - Franza, Andrea (2017)
Current needs for infrastructure and services in urban areas often require the construction of tunnels that may affect existing surface and buried structures. In general, the construction of new tunnels in the proximity of deep foundations raises concerns related to pile failure and associated structural damage (in both the superstructure and the foundation). Despite its practical importance, few studies have investigated the global tunnel-pile-structure interaction (TPSI) and, thus, engineers generally compensate for the lack of understanding with an overly conservative design approach.